2006
DOI: 10.4049/jimmunol.176.5.3028
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Frequency, Nonlinear Proliferation, and Functional Maturation of Virus-Specific CD4+ T Cells

Abstract: The early events regulating antiviral CD4 responses were tracked using an adoptive transfer model. CD4+ T cell expansion was nonlinear, with a lengthy lag phase followed by 2 days of explosive proliferation. A small number of naive Ag-specific CD4+ T cells were found in nonlymphoid tissues and, in the 8 days following infection, the number of activated cells increased in all tissues analyzed, and their effector functions matured. Finally, we show that a naive mouse contains ∼100 naive CD4+ precursor cells spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 69 publications
(157 reference statements)
13
99
0
Order By: Relevance
“…5A). Whitmire et al (19) have shown there are Ϸ100 GP61-specific naïve cells in B6 mice (19), and we found a similar number (160) after directly labeling total spleen and lymph node cells with IA b /GP61tet (Fig. S6).…”
Section: Memory Cells Either Generated By or Reactivated With Lymphocsupporting
confidence: 79%
See 2 more Smart Citations
“…5A). Whitmire et al (19) have shown there are Ϸ100 GP61-specific naïve cells in B6 mice (19), and we found a similar number (160) after directly labeling total spleen and lymph node cells with IA b /GP61tet (Fig. S6).…”
Section: Memory Cells Either Generated By or Reactivated With Lymphocsupporting
confidence: 79%
“…2C). Because we did not collect every LN, and there may have been some naïve IA b /3K-specific cells in the blood, this may be an underestimate, but this number is similar to that found in the Tg cell experiment and to that described for T cells with other specificities (19)(20)(21). To set a level of background staining, we examined tetramer staining of naïve CD4 T cells from mice that had been primed with an optimal dose of 3KϩLPS 7-9 days earlier.…”
Section: Memory Cd4 Cells Expand Less Efficiently Than Naïve Cells To Agsupporting
confidence: 53%
See 1 more Smart Citation
“…Initially, this was a surprising finding. However, the Ag-specific precursor frequency for naive T cells is ϳ1/1 ϫ 10 5 (100 cells/spleen) (68,69), a small population capable of significantly expanding and producing a sufficient protective adaptive immune response upon antigenic stimulation. This response ultimately leads to the survival of ϳ5% of the activated T cells (ϳ1 ϫ 10 5 cells) to serve as a memory pool after the contraction phase (69).…”
Section: Discussionmentioning
confidence: 99%
“…These effects can be grouped into 2 broad categories: (a) those affecting pMHCI abundance on the surface of APCs and (b) the number, recruitment, and proliferative capacity of naive epitope-specific CTLps that can engage in the response (1,6). The latter set of parameters has been especially difficult to measure, particularly when the naive CTLps are physiologically generated "endogenous" responders rather than TCR-Tg precursors (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%